Genetic Variability in Chilli(Capsicum annuum L.) with Emphasis to Reaction to Leaf Curl Virus - Leaya Jose (Department of Plant Breeding and Genetics, College of Agriculture, 2001)
The present investigation entitled "Genetic variability in chilli (Capsicum annuum L.) with emphasis to reaction to leaf curl virus" was conducted at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 2000-2001. The data for the investigation were collected from two field experiments, each laid out in Randomised Block Design with three replications. The second experiment was conducted without taking any control measures against leaf curl virus. The 37 genotypes included in the study showed significant difference for all the 15 traits. The maximum values for phenotypic coefficient of variation (pC V) genotypic coefficient of variation (GC V) were recorded for fruit yield per plant and the minimum values for crop duration. PCV and GCV were high for fruit yield per plant, number of fruits per plant, average fruit weight, vulnerability index, fruit girth and number of flowers per plant. These traits also showed high heritability coupled with high genetic advance. Yield per plant was positively correlated with number offruits per plant, average fruit weight, number of secondary branches, number of flowers per plant, fruiting span and crop duration. Path analysis revealed high positive direct effect for average fruit weight, number of fruits per plant and crop duration. Hence selection for these traits can improve yield.